Remediation of problematic residents—A national survey. (22nd September 2015) - Bhatti, Nasir I.; Ahmed, Aadil; Stewart, Michael G.; Miller, Robert H.; Choi, Sukgi S.
Abstract : Objectives/Hypothesis: Despite careful selection processes, residency programs face the challenge of training residents who fall below minimal performance standards. Poor performance of a resident can endanger both patient safety and the reputation of the residency program. It is important, therefore, for a program to identify such residents and implement strategies for their successful remediation. The purpose of our study was to gather information on evaluation and remediation strategies employed by different otolaryngology programs. Study Design: Cross‐sectional survey. Methods: We conducted a national survey, sending a questionnaire to the program directors of 106 otolaryngology residency programs. We collected information on demographics of the program, identification of problematic residents, and remediation strategies. Results: The response rate was 74.5%, with a 2% cumulative incidence of problematic residents in otolaryngology programs during the past 10 years. The most frequently reported deficiencies of problematic residents were unprofessional behavior with colleagues/staff (38%), insufficient medical knowledge (37%), and poor clinical judgment (34%). Personal or professional stress was the most frequently identified underlying problem (70.5%). Remediation efforts included general counseling (78%), frequent feedback sessions (73%), assignment of a mentor (58%), and extra didactics (47%). These remediation efforts failed to produce improvement in 23% of the identified residents, ultimately leading to their dismissal. Conclusions: The apparent deficiencies, underlying causes, and remediation strategies vary among otolaryngology residency programs. Based on the results of this survey, we offer recommendations for the early identification of problematic residents and a standardized remediation plan. Level of Evidence: NA Laryngoscope, 126:834–838, 2016